2021
DOI: 10.1002/jmv.27144
|View full text |Cite
|
Sign up to set email alerts
|

Soluble angiotensin‐converting enzyme 2 is transiently elevated in COVID‐19 and correlates with specific inflammatory and endothelial markers

Abstract: The main entry receptor of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is angiotensin‐converting enzyme 2 (ACE2). SARS‐CoV‐2 interactions with ACE2 may increase ectodomain shedding but consequences for the renin‐angiotensin system and pathology in Coronavirus disease 2019 (COVID‐19) remain unclear. We measured soluble ACE2 (sACE2) and sACE levels by enzyme‐linked immunosorbent assay in 114 hospital‐treated COVID‐19 patients compared with 10 healthy controls; follow‐up samples after four months… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 59 publications
8
64
1
2
Order By: Relevance
“…The meta-analysis that we carried out in the previous section has shed some light on these questions to a certain extent, but many points remain obscure. Indeed, the experimental and clinical data that we collected from the literature about e.g., the levels of proteins and peptides involved in RAS and the activity of the enzymes, partially disagree [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analysis that we carried out in the previous section has shed some light on these questions to a certain extent, but many points remain obscure. Indeed, the experimental and clinical data that we collected from the literature about e.g., the levels of proteins and peptides involved in RAS and the activity of the enzymes, partially disagree [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…We review here recent data about measurements of RAS components in COVID-19. For that purpose, we manually collected and screened a series of clinical and experimental results from [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94], listed in Supplementary Table S1. The individuals enrolled in these studies were classified into two or three classes: COVID-19 patients or severe and moderate COVID-19 patients, and controls or asymptomatic patients.…”
Section: Meta-analysis On Ras Components In Covid-19mentioning
confidence: 99%
“…In addition, it has also been observed that soluble ACE2 may contribute to COVID-19 susceptibility, although its significance remains uncertain. In this sense, subjects with obesity and patients with COVID-19 have higher serum ACE2 levels [56][57][58][59]. The increased soluble ACE2 levels in COVID-19 patients may result from the cellular lysis that occurs when a severe infection takes place.…”
Section: Influence Of Obesity and Ace2 In Covid-19 Beyond Ace2 Expressionmentioning
confidence: 99%
“…Recent studies demonstrated that ADAM-17-driven soluble ACE2 (sACE2) levels are elevated in COVID-19 patients. The binding of SARS-CoV-2 by sACE2 may enable cell entry of tissues where membrane-bound ACE2 (mACE2) is poorly expressed [65,66]. Low expression levels of mACE2 and associated higher ADAM-17 activity have been related with cardiovascular diseases.…”
Section: Risk Factors For Covid-19 and Defective Efferocytosismentioning
confidence: 99%
“…According to this perspective, while mACE2 may mediate cell entry of SARS-CoV-2, a genetically modified soluble form of ACE2, called human recombinant soluble angiotensin-converting enzyme-2 (hrsACE2), may decrease cell entry of SARS-CoV-2 competing for mACE2 [95]. However, the plasma RAS balance in COVID-19 patients was already characterized by a strong transient increase in circulating plasma sACE2 [66]. Therefore, in COVID-19 patients with comorbid diseases, both Angiotensin II and virus adversely affect the prognosis by affecting the RAS balance in a way that down-regulates ACE2 [96].…”
Section: Novel Treatment Options Targeting Defective Efferocytosis In Covid-19mentioning
confidence: 99%